Zakat and the Sustainable Development Goals: Fostering Socio-Economic Synergy in Gorontalo Regency (ZISWAF: Jurnal Zakat dan Wakaf, 2025)
Zakat, a pillar of the Islamic economic system, plays a vital role in sustainable development, particularly in Gorontalo Regency. Previous studies have largely focused on public interest in zakat, leaving its synergy with sustainable development—especially in economic and social dimensions—underexplored. This study examines the relationship between zakat and sustainable development, assessing its socio-economic impact. Using a descriptive and analytical approach, it explores zakat management and distribution while evaluating its contribution to the Sustainable Development Goals (SDGs). Findings indicate that zakat significantly contributes to poverty alleviation, education, and healthcare—three key SDG sectors. Economically, zakat functions as a wealth redistribution mechanism and a driver of local economic growth. Socially, it enhances community welfare and strengthens social cohesion. These impacts highlight zakat’s potential in advancing sustainable development. Further research is needed to explore innovative zakat management models that optimize its effectiveness and efficiency in achieving sustainable development goals.